Synthesis, Characterization and Mechanical Properties of ZrB2-based Composites in Zr-C-Si System for Ultra-high Temperature Applications - Jyoti (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Ceramic Engineering